Water Governance Analysis in the Development of Embung for Water Supply Security for Agriculture (Study in Sabu Raijua District, NTT Province) - Wadu, Jacob; Lay, Marthina Raga; Toda, Hendrik; Rihi, David Wilfrid; Nifu, Yabes I. (Journal of Social Research, 2023)
82.3% of the population of Sabu Raijua Regency work as farmers with a high level of need for water but the geographical conditions of Sabu Island are not able to support this activity because the majority consists of dry land with a percentage of 97.51% and the number of rainy days is only approximately 100 days per year so that The Sabu Raijua Regency Government has built hundreds of reservoirs to meet agricultural activities, but the weak sustainability of the reservoir construction projects in Sabu Raijua Regency is a problem in itself. The method used in this research is a descriptive method with a qualitative approach with a total number of 76 people who were determined purposively then the primary and secondary data collected were analyzed using data analysis techniques from Creswell (2016). Water governance in the construction of reservoirs for water supply resilience for agriculture in Sabu Raijua Regency, NTT Province uses theory from Van der Kerk, et al (2013: 8) with research results in aspects (1) content layer which is hampered by the uneven flow of information, the absence of training to improve the knowledge and skills of reservoir water users as well as poor strategies/policies, whereas in aspect (2) the institutional layer from the organizational side there was no clear division of roles and responsibilities between institutions, the private sector and the community relating to the use of reservoir water and instruments that were not adequate and in aspect (3) the relational layer on the cooperation side was found not to involve existing policy stakeholders in making decisions about the water management process. The inhibiting factors for water governance in the construction of reservoirs for the resilience of water supply for agriculture in Sabu Raijua Regency, NTT Province consist of a minimal budget, lack of effective institutional governance and climate and geographical conditions.